Youth work and “youth at risk” in the Netherlands - Evelyne Baillergeau; Marc Hoijtink (Sociétés et Jeunesses en Difficulté)
The point of this article is to explore the rationales for action of frontline social professionals who are dealing with marginal young people : What is actually done about marginality, beyond policy intentions and social practice ? This question is addressed on the basis of a literature review into youth work in the Netherlands. First, the development of youth work as a field of social practice is outlined as well as the extent to which the issue of the marginalised youth has been addressed by youth workers all along the 20th century. Second, the current challenges for Dutch youth work regarding «deprived youth» are explored together with the position of the Dutch youth workers within in the context of the «hard line» discussion according to the available literature. The article shows that persistent attention has been paid to marginal youth as a social problem in the academic and professional world over the last decades. However, there is amazingly little academic knowledge about youth work with regard to marginalized youth in spite of the topicality of the issue of «youth at risk» in the Netherlands and despite the fact that many observers state that youth workers have a role to play regarding the current problems of «youth at risk».